Method for connecting ceramic / glass and metal through laser surface modification technology

Through laser surface modification technology, a metallized layer is formed on the surface of the ceramic/glass sheet, solving the problems of insufficient wetting, residual stress, mismatch in physical properties and metallurgy incompatibility in the connection between ceramic and metal, glass and metal, and achieving high quality ceramic/glass is connected to metal.

CN119461893AActive Publication Date: 2025-02-18HARBIN INST OF TECH AT WEIHAI +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411693360.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The connection between ceramics and metals and glasses faces problems such as insufficient wetting, residual stress, mismatch in physical properties and metallurgy incompatibility, resulting in poor connection effect.

Method used

Laser surface modification technology is used to coat the surface of the ceramic/glass sheet with a precursor solution, and a metallization layer is formed by laser irradiation to promote the eutectic or metallurgical reaction between the ceramic/glass and metal to achieve a firm connection.

Benefits of technology

Through laser surface modification technology, the connection strength and reliability of ceramic/glass and metal are improved, residual stress and energy consumption are reduced, and the obtained joint has good mechanical properties and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461893A_ABST
    Figure CN119461893A_ABST
Patent Text Reader

Abstract

The invention provides a method for connecting ceramic / glass and metal through a laser surface modification technology. The method solves the technical problems that an existing ceramic / glass and metal connecting interface is insufficient in infiltration, unmatched in residual stress and physical property and incompatible in metallurgy. Comprising the following steps: S1, cleaning, grinding and polishing a ceramic sheet / glass sheet; s2, coating the precursor solution on the surface of a ceramic sheet / glass sheet, and drying to form a precursor layer; the solute of the precursor solution is easy-to-decompose nitric acid metal salt or precious metal acid salt and a reducing agent, and the solvent is water; s3, after the precursor layer is irradiated by laser, cleaning and drying the ceramic sheet / glass sheet to obtain a surface-modified ceramic sheet / glass sheet; s4, under vacuum, assembling the surface-modified ceramic sheet / glass sheet and the polished metal sheet according to a sequence of ceramic sheet / glass sheet-metal sheet or ceramic sheet / glass sheet-brazing filler metal-metal sheet, overlapping and compressing to form an assembly, and cooling to room temperature; the method can be widely applied to the technical field of ceramic / glass and metal connection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic / glass and metal connection, and in particular to a method for connecting ceramic / glass and metal using laser surface modification technology. Background Art

[0002] Ceramic materials have the advantages of high hardness, high wear resistance, high corrosion resistance and good high temperature performance, while metal materials have high strength, good ductility and electrical and thermal conductivity, forming an obvious complementary relationship with ceramic materials in terms of performance, especially in high-tech fields such as semiconductor packaging, aerospace, and power electronics. With the advancement of science and technology and the development of industry, ceramic-metal connectors are increasingly used in new energy vehicles, electronic and electrical, semiconductor packaging, IGBT modules and other fields. For example, the large-scale industrialization of a series of products such as ceramic relays, ceramic sealed connectors, and ceramic substrates has put forward higher requirements for ceramic-metal connection technology. Due to the significant differences in the physical and chemical properties of ceramics and metals, such as thermal expansion coefficient, wettability, and chemical stability, these differences make the connection between ceramics and metals a challenging task. The connection technology between ceramics and metals faces many challenges, mainly including the following two aspects: ceramic materials are mainly composed of ionic bonds and covalent bonds, and there are significant differences in chemical properties with metal materials mainly composed of metallic bonds, resulting in almost no wetting between the two; the thermal expansion coefficients of ceramics and metals are generally quite different, and when the temperature changes, residual stress is easily generated at the connection interface, resulting in connection failure.

[0003] Glass materials, with their excellent high temperature resistance, corrosion resistance, unparalleled transparency and light transmittance, are perfectly combined with metal materials, bringing unprecedented innovation opportunities to the high-tech field. The connection between glass and metal has shown a wide range of application value in cutting-edge scientific and technological fields such as microelectronics, optics, and aerospace. This combination not only extends the service life of the device, but also more effectively prevents the failure and loss of connection of the equipment in harsh environments, providing a solid safety guarantee for scientific and technological progress and engineering applications. The connection between glass and metal faces two basic problems: physical property mismatch and metallurgical incompatibility. Among them, physical property mismatch is mainly reflected in the differences in physical properties such as thermal expansion coefficient and elastic modulus, which may cause stress concentration at the connection interface when the temperature changes or is subjected to force, thereby affecting the reliability of the connection; while metallurgical incompatibility is the primary problem in achieving metallurgical bonding between glass and metal, because glass and metal have significant differences in atomic structure and chemical bonding mode, and it is difficult to achieve a strong bond through traditional metallurgical methods.

[0004] It can be seen that the main technical problems of ceramic-metal connection interface are insufficient wetting and residual stress, and the main technical problems of glass-metal connection interface are physical property mismatch and metallurgical incompatibility. This technical problem needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to solve the deficiencies of the above-mentioned technologies and to provide a method for connecting ceramic / glass and metal using laser surface modification technology to improve the connection effect between the ceramic / glass and metal connection interfaces.

[0006] To this end, the present invention provides a method for connecting ceramic / glass and metal using laser surface modification technology, comprising the following steps:

[0007] Step S1. Wash, grind and polish the ceramic / glass sheet.

[0008] Step S2. Coat the surface of the ceramic sheet / glass sheet obtained in step S1 with a precursor solution, and then dry it to form a precursor layer; in the precursor solution, the solute is an easily decomposable metal nitrate or noble metal acid salt, a reducing agent, and the solvent is water.

[0009] Step S3. The precursor layer formed on the surface of the ceramic sheet / glass sheet obtained in step S2 is subjected to laser irradiation, and then the ceramic sheet / glass sheet is washed and dried to obtain a surface-modified ceramic sheet / glass sheet.

[0010] On the one hand, laser irradiation is used to provide energy for the generation of metal elements in the precursor layer and the surface remelting of ceramics / glass or the generation of metal elements, wherein the reducing agent in the precursor layer reduces the metal ions in the metal nitrate or precious metal salt to the corresponding metal elements under laser irradiation, and forms metal particles on the surface of the ceramics / glass; the surface of the ceramics / glass is remelted or decomposed into metal elements under laser irradiation, wherein the remelted ceramics / glass that are usually not easily decomposed by laser irradiation, such as K9 glass, alumina ceramics, silicon carbide ceramics, etc. The metal element decomposed is a ceramic / glass that is easily decomposed by laser irradiation, such as silicon nitride ceramic decomposition of silicon, aluminum nitride ceramic decomposition of aluminum, etc., and then a eutectic or metallurgical reaction occurs with the metal element decomposed from the precursor; on the other hand, the surface of the surface-modified ceramic / glass sheet prepared under laser irradiation is covered with a large number of tiny pits that are the same as the laser path, which increases the contact area, thereby improving the bonding force of the contact surface, preparing for step S4; especially when using solder, the welding area is increased, and there is a certain regulatory effect on the stress distribution of the joint welding. Step S4. Under a vacuum environment, the surface-modified ceramic / glass sheet obtained in step S3 and the polished metal sheet are assembled in the order of ceramic / glass sheet-metal sheet or ceramic / glass sheet-brazing material-metal sheet, overlap and press to form an assembly under a certain heating temperature and pressure, and cool to room temperature to achieve the connection between the ceramic / glass sheet and the metal sheet. The modified ceramic sheet / glass sheet and the metal sheet or both of them and the brazing material interact at high temperature to diffuse with each other or form a local liquid phase. As the temperature gradually decreases, these liquid phases solidify, thereby forming a strong metallurgical bond between the ceramic sheet / glass sheet and the metal sheet.

[0011] Preferably, in step S1, the ceramic sheet is one of an oxide ceramic sheet, a nitride ceramic sheet, and a carbide ceramic sheet.

[0012] Preferably, in step S1, the ceramic sheet / glass sheet is ultrasonically cleaned in an anhydrous alcohol solution, and the surface of the ceramic sheet / glass sheet is gradually ground to 2000 mesh using a diamond sand disc, and then polished.

[0013] Preferably, in step S2, in the precursor solution, the concentration of the solute is 300-600 g / L, the metal nitrate is copper nitrate or silver nitrate, the noble metal acid salt is one or more of palladium nitrate, copper acetate, silver citrate, and chloroauric acid; the reducing agent is one or more of polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and polyacrylonitrile (PAN), and its concentration is 90-150 g / L; the solvent is one of purified water, deionized water, and distilled water. The reducing agent PVP decomposes into methylamine, propionic acid, and carboxylic acid under laser irradiation, and the carboxylic acid obtained by the decomposition, as well as the nitrile group of the reducing agent polyethylene glycol and polyacrylonitrile itself have certain reducing properties, so that the metal ions in the metal nitrate salts such as copper nitrate and silver nitrate are respectively reduced to the corresponding metal elements such as copper and silver, and the metal ions in the noble metal acid salts such as palladium nitrate and copper acetate are respectively reduced to the corresponding metal elements such as palladium and copper.

[0014] Preferably, in step S3, the laser is a continuous laser, the continuous laser power is 1 to 100 W, and the scanning rate is 1 to 5000 mm / min.

[0015] Preferably, in step S3, the laser is a pulse laser, the pulse laser power is 1 to 120 W, the laser pulse width is 1 to 400 ms, the laser frequency is 1 to 1000 kHz, and the laser scanning speed is 1 to 5000 mm / min.

[0016] Preferably, in step S3, the processing environment of the ceramic sheet / glass sheet is one of an atmospheric atmosphere, a vacuum atmosphere, and an inert gas atmosphere.

[0017] Preferably, in step S4, the metal sheet is one of a titanium sheet, an aluminum sheet, a copper sheet, an aluminum alloy sheet, a copper alloy sheet, a titanium alloy sheet, and a stainless steel sheet; and the solder is one of a tin-based solder, an aluminum-based solder, and a silver-based solder.

[0018] Preferably, in step S4, the vacuum degree in the vacuum hot pressing furnace is 1×10 -3 Pa~7×10 -3 Pa.

[0019] Preferably, in step S4, the axial pressure applied by stacking and pressing to form the assembly is not greater than 6 MPa. The axial force refers to the force perpendicular to the stacking connection surface of the ceramic sheet / glass sheet and the metal sheet, and if brazing is used, it refers to the force perpendicular to the brazing surface.

[0020] Preferably, in step S4, the heating rate is 5-20°C / min, the heating temperature is 400-1000°C, the holding time is 1-60min, and the cooling rate is 5°C / min.

[0021] The present invention provides a method for connecting ceramic / glass and metal using laser surface modification technology, which has the following beneficial effects:

[0022] (1) The surface of a ceramic sheet / glass sheet with a precursor is modified by laser. On the one hand, the precursor is decomposed and reduced to a metal element, and the ceramic / glass surface is decomposed after modification, such as silicon nitride is decomposed into silicon element, aluminum nitride is decomposed into aluminum element, etc., thereby forming a metallization layer; a local liquid phase is formed by eutectic reaction to achieve diffusion connection between ceramic and metal at a lower temperature; or the metallization layer is used to achieve wetting of ceramic / glass by inactive solder, thereby achieving medium-temperature or low-temperature brazing of ceramic / glass and metal; thereby solving the technical defect of large thermal stress and affecting joint performance in the existing connection between ceramic / glass sheets and metal; on the other hand, the ceramic / glass surface is modified to form a metallization layer, which effectively promotes the wetting of inactive solder on ceramic / glass, further enriching the connection technology between ceramic / glass and metal.

[0023] (2) The ceramic / glass surface is modified by laser irradiation, which effectively changes the chemical composition and surface state of the ceramic / glass surface, forms a metallization layer on the surface of the ceramic / glass, and interacts with the precursor layer to achieve high-quality connection between ceramic / glass and metal at a lower temperature, thereby reducing energy consumption. The preparation method is green and environmentally friendly. The obtained ceramic / glass-metal joint has the advantages of low residual stress, uniform mechanical properties and high reliability, which successfully solves the technical problems in the connection between ceramic / glass and metal. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application.

[0025] Figure 1 a), Figure 1 c) are macroscopic photographs of the aluminum nitride ceramic sheet before and after surface modification in Example 1 of the present invention; Figure 1 b) Figure 1 d) are scanning electron microscope photos of the aluminum nitride ceramic sheet before and after surface modification according to Example 1 of the present invention;

[0026] Figure 2 This is a scanning electron microscope photograph of the connection interface between the aluminum nitride ceramic sheet and the metal aluminum in Example 1 of the present invention;

[0027] Figure 3 a), Figure 3 b) are conductivity test photos of K9 glass before and after surface modification in Example 3 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application. The methods used in the present invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercial products unless otherwise specified.

[0029] Embodiment 1:

[0030] This embodiment provides a method for connecting ceramic and metal using laser surface modification technology, comprising the following steps:

[0031] Step 1: Select an aluminum nitride ceramic sheet as the ceramic sheet, put the aluminum nitride ceramic sheet into an anhydrous alcohol solution for ultrasonic cleaning for 10 minutes to remove surface impurities and dirt, and then use diamond sand discs with different mesh sizes to grind the surface of the aluminum nitride ceramic sheet step by step to 2000 mesh, and polish it.

[0032] Step 2: Coat the aluminum nitride ceramic sheet obtained in step 1 with a 1 mm thick precursor solution, the precursor composition of which is 500 g / L Cu(NO3)2, 100 g / L PVP, and the solvent is deionized water; then place the coated material in a drying oven and dry it at 50°C for 1 hour.

[0033] Step 3: Place the aluminum nitride ceramic sheet in step 2 on a laser processing platform, and irradiate the surface of the aluminum nitride ceramic sheet with laser in an atmospheric atmosphere, wherein the laser is a continuous laser, the laser power is 25W, and the laser scanning speed is 100mm / min, so as to achieve surface modification of the ceramic sheet, and a metallization layer is generated on the surface thereof, which is mainly composed of Cu and Al, and is derived from the decomposition of the aluminum nitride ceramic into N2 and Al under the action of the laser and the Cu reduced from the precursor; the processed aluminum nitride ceramic sheet is placed in an anhydrous alcohol solution for ultrasonic cleaning for 20 minutes to remove the processing residues on the surface of the ceramic sheet, and is dried in a drying oven at 50°C for 1 hour.

[0034] Step 4: Assemble the surface-modified aluminum nitride ceramic sheet obtained in step 3 and the polished aluminum sheet in the order of ceramic sheet-aluminum sheet and place them in a vacuum hot pressing furnace, apply an axial pressure of 3 MPa to the assembly of the aluminum nitride ceramic sheet and the aluminum sheet, and wait until the vacuum degree reaches 2×10 -3Pa, first heated to 500°C at a heating rate of 20°C / min and kept warm for 10 min, then heated to 600°C at a heating rate of 10°C / min and kept warm for 30 min, finally cooled to 300°C at a cooling rate of 5°C / min and cooled with the furnace, the Cu-Al metallization layer and the Al sheet undergo eutectic reaction, that is, the connection between the aluminum nitride ceramic sheet and the metal copper sheet is achieved, and the obtained ceramic-metal joint has good bonding.

[0035] Embodiment 2:

[0036] This embodiment provides a method for connecting ceramic and metal using laser surface modification technology, comprising the following steps:

[0037] Step 1: Select a silicon nitride ceramic sheet, put the silicon nitride ceramic sheet into an anhydrous alcohol solution for ultrasonic cleaning for 10 minutes to remove surface impurities and dirt, and then use diamond sand discs with different mesh sizes to grind the surface of the silicon nitride ceramic sheet step by step to 2000 mesh, and polish it.

[0038] Step 2: Coat the silicon nitride ceramic sheet obtained in step 1 with a 1.5 mm thick precursor solution, wherein the precursor composition is 300 g / L AgNO3, 50 g / L PVP and 60 g / L PAN, and the solvent is deionized water; then place the coated material in a drying oven and dry it at 50°C for 1 hour.

[0039] Step three, place the silicon nitride ceramic sheet in step two on a laser processing platform, and irradiate the surface of the silicon nitride ceramic sheet with laser in an atmospheric atmosphere, wherein the laser is a pulsed laser with a laser power of 70W, a laser pulse width of 75ms, a laser frequency of 100kHz, and a laser scanning speed of 200mm / min, so as to achieve surface modification of the ceramic sheet, and generate a metallization layer on the surface thereof, which is mainly composed of Ag and Si, and is derived from the decomposition of silicon nitride ceramic into N2 and Si under the action of laser and the Ag reduced from the precursor; the processed silicon nitride ceramic sheet is placed in an anhydrous alcohol solution for ultrasonic cleaning for 20 minutes to remove the processing residues on the surface of the ceramic sheet, and is dried in a drying oven at 50°C for 1 hour.

[0040] Step 4: Assemble the surface-modified silicon nitride ceramic sheet obtained in step 3 and the polished copper sheet in the order of ceramic sheet-copper sheet and place them in a vacuum hot pressing furnace, apply an axial pressure of 6 MPa to the assembly of the silicon nitride ceramic sheet and the copper sheet, and wait until the vacuum degree reaches 2×10 -3Pa, first heated to 700°C at a heating rate of 20°C / min and kept warm for 10 min, then heated to 800°C at a heating rate of 10°C / min and kept warm for 60 min, finally cooled to 300°C at a cooling rate of 5°C / min and cooled with the furnace, the Ag-Si metallization layer and the copper sheet undergo eutectic reaction, that is, the connection between the silicon nitride ceramic sheet and the metal copper sheet is achieved, and the obtained ceramic-metal joint has good bonding.

[0041] Embodiment 3:

[0042] This embodiment provides a method for connecting glass and metal using laser surface modification technology, comprising the following steps:

[0043] Step 1: Select a K9 glass sheet and place it in an anhydrous alcohol solution for ultrasonic cleaning for 10 minutes to remove surface impurities and dirt. Then use diamond sandpaper with different mesh sizes to grind the surface of the K9 glass sheet step by step to 2000 mesh and polish it.

[0044] Step 2: Coat the K9 glass sheet obtained in step 1 with 1 mm of precursor solution, the precursor composition of which is 600 g / L Cu(NO3)2, 120 g / L PVP, and the solvent is deionized water; then place the coated material in a drying oven and dry it at 50°C for 1 hour.

[0045] Step 3, place the K9 glass sheet in step 2 on a laser processing platform, and irradiate the surface of the K9 glass sheet with laser in an argon atmosphere, wherein the laser is a pulsed laser, the laser power is 50W, the laser pulse width is 250ms, the laser frequency is 200kHz, and the laser scanning speed is 200mm / min to achieve surface modification of the glass, and a copper metallization layer is generated on its surface. The metallization layer is conductive and has a resistance of 3.2Ω after testing; the processed K9 glass sheet is placed in an anhydrous alcohol solution for ultrasonic cleaning for 20 minutes to remove the processing residues on the glass surface, and is dried in a drying oven at 50°C for 1 hour.

[0046] Step 4: The surface-modified K9 glass sheet obtained in step 3 and the polished aluminum sheet are assembled in the order of ceramic sheet-aluminum sheet and placed in a vacuum hot press furnace. An axial pressure of 1 MPa is applied to the assembly of the K9 glass sheet and the aluminum sheet. When the vacuum degree reaches 5×10 -3 Pa, firstly heated to 300°C at a heating rate of 20°C / min and kept at this temperature for 10 min, then heated to 400°C at a heating rate of 10°C / min and kept at this temperature for 60 min, and finally cooled to 300°C at a cooling rate of 5°C / min and then cooled with the furnace, the Cu metallization layer and the Al sheet diffused and reacted, that is, the connection between the K9 glass sheet and the metal copper sheet was achieved, and the obtained glass-metal joint had good bonding.

[0047] Embodiment 4:

[0048] This embodiment provides a method for connecting ceramic and metal using laser surface modification technology, comprising the following steps:

[0049] Step 1: Select an alumina ceramic sheet, put the alumina ceramic sheet into an anhydrous alcohol solution for ultrasonic cleaning for 10 minutes to remove surface impurities and dirt, and then use diamond sand discs with different mesh sizes to grind the surface of the alumina ceramic sheet step by step to 2000 mesh, and polish it.

[0050] Step 2: Coat the alumina ceramic sheet obtained in step 1 with a 1.5 mm thick precursor solution, wherein the precursor composition is 600 g / L Cu(NO3)2, 100 g / L PVP and 50 g / L PEG, and the solvent is deionized water; then place the coated material in a drying oven and dry it at 50°C for 1 hour.

[0051] Step three, place the alumina ceramic sheet in step two on a laser processing platform, and irradiate the surface of the alumina ceramic sheet with laser in an atmospheric atmosphere, wherein the laser is a continuous laser, the laser power is 40W, and the laser scanning speed is 500mm / min, so as to achieve surface modification of the ceramic sheet, and a copper metallization layer is generated on its surface. The metallization layer is conductive and its resistance is 3.5Ω after testing; the processed alumina ceramic sheet is placed in anhydrous alcohol solution for ultrasonic cleaning for 20 minutes to remove the processing residues on the surface of the ceramic sheet, and dried in a drying oven at 50°C for 1 hour.

[0052] Step 4: Assemble the surface-modified alumina ceramic sheet obtained in step 3 with the polished aluminum sheet and Al88Si12 brazing filler metal in the order of ceramic sheet-brazing filler metal-aluminum sheet and place them in a vacuum hot pressing furnace without applying axial pressure until the vacuum degree reaches 2×10 -3 Pa, first heated to 500°C at a heating rate of 20°C / min and kept warm for 10 min, then heated to 600°C at a heating rate of 10°C / min and kept warm for 20 min, finally cooled to 300°C at a cooling rate of 5°C / min and cooled with the furnace. With the promotion of the copper metallization layer, the wetting of the brazing material on the alumina ceramic sheet was achieved, that is, the connection between the alumina ceramic sheet and the metal aluminum sheet was achieved at 600°C, and the obtained ceramic-metal joint was well bonded.

[0053] Embodiment 5:

[0054] This embodiment provides a method for connecting ceramic and metal using laser surface modification technology, comprising the following steps:

[0055] Step 1: Select a silicon carbide ceramic sheet as the ceramic sheet, put the silicon carbide ceramic sheet into an anhydrous alcohol solution for ultrasonic cleaning for 10 minutes to remove surface impurities and dirt, and then use diamond sand discs with different mesh sizes to grind the surface of the silicon carbide ceramic sheet step by step to 2000 mesh, and polish it.

[0056] Step 2: Coat the silicon carbide ceramic sheet obtained in step 1 with a 2 mm thick precursor solution, the precursor composition of which is 400 g / L AgNO3, 20 g / L PEG and 70 g / L PAN, and the solvent is deionized water; then place the coated material in a drying oven and dry it at 50°C for 1 hour.

[0057] Step 3, placing the silicon carbide ceramic sheet in step 2 on a laser processing platform, and irradiating the surface of the silicon carbide ceramic sheet with laser in a vacuum atmosphere, wherein the laser is a pulsed laser, the laser power is 80W, the laser pulse width is 100ms, the laser frequency is 20kHz, and the laser scanning speed is 150mm / min, so as to achieve surface modification of the ceramic sheet, and a continuous silver metallization layer is generated on its surface. The metallization layer is conductive and its resistance is 2.3Ω after testing; the processed silicon carbide ceramic sheet is placed in anhydrous alcohol solution for ultrasonic cleaning for 20min to remove the processing residue on the surface of the ceramic sheet, and dried in a drying oven at 50°C for 1h.

[0058] Step 4: Assemble the surface-modified silicon carbide ceramic sheet obtained in step 3, the polished titanium sheet and AgCuIn20-31 solder in the order of ceramic sheet-solder-titanium sheet and place them in a vacuum hot pressing furnace without applying axial pressure until the vacuum degree reaches 1.5×10 -3 Pa, first heated to 500°C at a heating rate of 20°C / min and kept warm for 10 min, then heated to 700°C at a heating rate of 10°C / min and kept warm for 30 min, finally cooled to 300°C at a cooling rate of 5°C / min and cooled with the furnace. With the promotion of the silver metallization layer, the wetting of the brazing material on the silicon carbide ceramic sheet is achieved, that is, the connection between the silicon carbide ceramic sheet and the metal titanium sheet is achieved at 700°C, and the obtained ceramic-metal joint has good bonding.

[0059] Experimental test:

[0060] Figure 1 a), Figure 1 c) are macroscopic photos of the aluminum nitride ceramic sheet before and after surface modification in Example 1 of the present invention. Figure 1 As shown in a), the original aluminum nitride ceramic is white; Figure 1 As shown in Figure c), black and silver-white substances appeared on the surface of the aluminum nitride ceramic sheet after surface modification, indicating that the laser surface modification effect is obvious and new substances are generated.

[0061] Figure 1b) Figure 1 d) are scanning electron microscope photos of the aluminum nitride ceramic sheet before and after surface modification in Example 1 of the present invention. Figure 1 As shown in b), the aluminum nitride ceramic sheet before surface modification is composed of gray aluminum nitride ceramic particles and a small amount of white yttrium oxide sintering agent; Figure 1 As shown in d), after the surface modification of the aluminum nitride ceramic sheet, a layer of grayish-white substance is added to the surface, indicating that after the laser surface modification, a metal element or intermetallic compound layer is formed on the surface of the aluminum nitride ceramic sheet. In addition, the surface of the aluminum nitride ceramic sheet is covered with a large number of tiny pits.

[0062] Figure 2 This is a scanning electron microscope photo of the connection interface between the aluminum nitride ceramic sheet and the metal aluminum sheet in Example 1 of the present invention. Figure 2 As shown, the diffusion welding joint has no defects such as cracks and holes, indicating that the surface-modified aluminum nitride ceramic sheet and the metal aluminum sheet are well bonded.

[0063] Figure 3 a), Figure 3 b) are the conductivity test photos of the K9 glass sheet before and after surface modification in Example 3 of the present invention. Figure 3 As shown in a), after multimeter testing, K9 glass does not have conductivity; Figure 3 As shown in b), after the multimeter test, the surface resistance of the treated K9 glass is 3.2Ω, indicating that there is a continuous copper layer on the surface of the K9 glass after laser surface modification, and the surface metallization is achieved.

[0064] It should be noted that:

[0065] (1) The laser used in the present invention is a continuous laser or a pulsed laser. When the laser is a continuous laser, the continuous laser power is 1 to 100 W, and the scanning rate is 1 to 5000 mm / min; when the laser is a pulsed laser, the pulsed laser power is 1 to 120 W, the laser pulse width is 1 to 400 ms, the laser frequency is 1 to 1000 kHz, and the laser scanning speed is 1 to 5000 mm / min. It can be selected according to actual conditions.

[0066] (2) The cleaning method, time, drying time, temperature, etc. of the present invention are determined according to actual conditions. The room temperature of the present invention is 20°C ± 5°C.

[0067] (3) When assembling the surface-modified ceramic sheet with the polished metal sheet, tin-based solder, aluminum-based solder or silver-based solder can be selected according to the actual situation.

[0068] (4) The ceramic sheet used in step 1 of the above embodiment can be one of an oxide ceramic sheet, a nitride ceramic sheet, and a carbide ceramic sheet. The K9 glass sheet described in embodiment 3 is a type of glass, and other glass sheets can also be used as a substitute.

[0069] (5) Among the precursor components of step 2 of the above embodiment, the silver nitrate and copper nitrate used have poor thermal stability and are easily decomposed by heat to form oxides, which are then reduced to metal elements by a reducing agent. Other easily decomposable metal nitrates or precious metal salts can also replace silver nitrate and copper nitrate, including easily decomposable metal nitrates such as palladium nitrate, and easily decomposable precious metal salts such as palladium nitrate, copper acetate, silver citrate, chloroauric acid, etc.

[0070] (6) Deionized water is used in step 2 of the above embodiment, but purified water or distilled water may be used instead.

[0071] (7) The vacuum atmosphere in step 3 of the above embodiment may also be an atmospheric atmosphere or an inert gas atmosphere.

[0072] (8) The aluminum sheet, copper sheet, and titanium sheet in step 4 of the above embodiment may also be replaced by aluminum alloy sheets, copper alloy sheets, titanium alloy sheets, stainless steel sheets, and other metals. The brazing material may also be tin-based brazing material, aluminum-based brazing material, silver-based brazing material, and other brazing materials. The vacuum degree in the vacuum hot pressing furnace is preferably 1×10 -3 Pa~7×10 -3 Pa. The heating rate, heating temperature, holding time and cooling rate can be set according to actual conditions. Preferably, the heating rate is 5-20°C / min, the heating temperature is 400-1000°C, the holding time is 1-60min, and the cooling rate is 5°C / min.

[0073] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for connecting ceramic / glass and metal using laser surface modification technology, characterized in that: The following steps are involved: Step S1. Wash, grind and polish the ceramic / glass sheet; Step S2. coating the precursor solution on the surface of the ceramic sheet / glass sheet obtained in step S1, and drying to form a precursor layer; in the precursor solution, the solute is an easily decomposable metal nitrate or noble metal acid salt, a reducing agent, and the solvent is water; Step S3. irradiating the precursor layer formed on the surface of the ceramic sheet / glass sheet obtained in step S2 with a laser, and then washing and drying the ceramic sheet / glass sheet to obtain a surface-modified ceramic sheet / glass sheet; Step S4. Under a vacuum environment, assemble the surface-modified ceramic sheet / glass sheet obtained in step S3 and the polished metal sheet in the order of ceramic sheet-metal sheet or ceramic sheet / glass sheet-brazing material-metal sheet, overlap and press them under a certain heating temperature and pressure to form an assembly, and cool them to room temperature to achieve the connection between the ceramic sheet / glass sheet and the metal sheet.

2. The method for connecting ceramic / glass and metal by laser surface modification technology according to claim 1, characterized in that: In the step S1, the ceramic sheet is one of an oxide ceramic sheet, a nitride ceramic sheet, and a carbide ceramic sheet.

3. The method for connecting ceramic / glass and metal by laser surface modification technology according to claim 1, characterized in that: In the step S1, the ceramic sheet / glass sheet is ultrasonically cleaned in an anhydrous alcohol solution, and the surface of the ceramic sheet / glass sheet is ground step by step to 2000 mesh using a diamond sand disc, and then polished.

4. The method for connecting ceramic / glass and metal by laser surface modification technology according to claim 1, characterized in that: In step S2, in the precursor solution, the concentration of the solute is 300-600 g / L, the metal nitrate is copper nitrate or silver nitrate, and the noble metal acid salt is one or more of palladium nitrate, copper acetate, silver citrate, and chloroauric acid; the reducing agent is one or more of polyvinyl pyrrolidone, polyethylene glycol, and polyacrylonitrile, and its concentration is 90-150 g / L; the solvent is one of purified water, deionized water, and distilled water.

5. The method for connecting ceramic / glass and metal by laser surface modification technology according to claim 1, characterized in that: In step S3, the laser is a continuous laser, the continuous laser power is 1 to 100 W, and the scanning rate is 1 to 5000 mm / min; Alternatively, the laser is a pulse laser, the pulse laser power is 1 to 120 W, the laser pulse width is 1 to 400 ms, the laser frequency is 1 to 1000 kHz, and the laser scanning speed is 1 to 5000 mm / min.

6. The method for connecting ceramic / glass and metal by laser surface modification technology according to claim 1, characterized in that: In the step S3, the processing environment of the ceramic sheet / glass sheet is one of an atmospheric atmosphere, a vacuum atmosphere, and an inert gas atmosphere.

7. The method for connecting ceramic / glass and metal by laser surface modification technology according to claim 1, characterized in that: In step S4, the metal sheet is one of a titanium sheet, an aluminum sheet, a copper sheet, an aluminum alloy sheet, a copper alloy sheet, a titanium alloy sheet, and a stainless steel sheet; the solder is one of a tin-based solder, an aluminum-based solder, and a silver-based solder.

8. The method for connecting ceramic / glass and metal by laser surface modification technology according to claim 1, characterized in that: In step S4, the vacuum degree in the vacuum hot pressing furnace is 1×10 -3 Pa~7×10 -3 Pa.

9. The method for connecting ceramic / glass and metal by laser surface modification technology according to claim 1, characterized in that: In step S4, the axial pressure applied by stacking and pressing to form the assembly is no greater than 6 MPa.

10. The method for connecting ceramic / glass and metal using laser surface modification technology according to claim 1, characterized in that: In step S4, the heating rate is 5-20°C / min, the heating temperature is 400-1000°C, the holding time is 1-60min, and the cooling rate is 5°C / min.

Citation Information

Patent Citations

  • Preparation method of copper-clad film precursor on aluminum nitride and copper-clad film precursor on aluminum nitride, and copper-clad film on aluminum nitride and preparation method thereof

    CN101875569A

  • Method of selective metallization on ceramic surface

    CN103253988A

  • Laser-assisted method for preparing ceramic and metal composite substrate and composite substrate

    CN117550910A

  • Aluminium nitride sintered body formed with metallized layer and method of manufacturing the same

    EP0276788A2

  • Method of forming metal coating film on ceramic base material surface and metallized ceramic base material

    JP2006052101A